Inter-Disciplinary Approach in Archival Curriculums of Archival Study Programs in Indonesia - Rina Rakhmawati; Elya Riska Dwi Wahyuni (UPT Perpustakaan UIN Alauddin Makassar, 2023)
This paper aims to describe the curriculum model applied in archival study programs in Indonesia, also analyze the influence of several disciplines in the core courses of the archival study programs. Analysis was carried out on documents containing courses that accessed through archival institutions and archival study program portals at each high-education institution. The data used are academic guidance documents and transcript of in-depth interviews with study program managers. Data were analyzed using a case study approach focused on archival study programs at Gadjah Mada University, Diponegoro University, and Universitas Terbuka. The results of this study are that the archival study program at Gadjah Mada University has a curriculum style dominated by the influence of two disciplines, history and administration science. The domination of both disciplines is none other than the study program founders who have a scientific background history, as well as the paradigm that used by the National Archives of the Republic of Indonesia, as an archival supervisory institution at the national level. As for Diponegoro University and Universitas Terbuka, they tend to be dominated not only by administration and management science, but also information and library science, as well as communication science. This is inseparable from the educational background of the lecturers and the scientific style of the faculties of each study program.